2013
DOI: 10.7448/ias.16.1.17994
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and factors associated with adherence to and completion of combination antiretroviral therapy for prevention of mother to child transmission in western Kenya

Abstract: IntroductionThe objective of this analysis was to identify points of disruption within the prevention of mother-to-child transmission (PMTCT) continuum from combination antiretroviral therapy (CART) initiation until delivery.MethodsTo address this objective, the electronic medical records of all antiretroviral-naïve adult pregnant women who were initiating CART for PMTCT between January 2006 and February 2009 within the Academic Model Providing Access To Healthcare (AMPATH), western Kenya, were reviewed. Outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
34
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 36 publications
6
34
2
Order By: Relevance
“…Although retention-related outcome definitions vary between studies, these findings are broadly consistent with the results of previous publications indicating high levels of non-retention and/or non-adherence, particularly postpartum [ 15 , 26 , 28 30 ]. The rate of disengagement appeared higher in the ANC ART site post-delivery and lower in the ANC ART site prior to delivery, compared to rates among women in the general ART clinic.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although retention-related outcome definitions vary between studies, these findings are broadly consistent with the results of previous publications indicating high levels of non-retention and/or non-adherence, particularly postpartum [ 15 , 26 , 28 30 ]. The rate of disengagement appeared higher in the ANC ART site post-delivery and lower in the ANC ART site prior to delivery, compared to rates among women in the general ART clinic.…”
Section: Discussionsupporting
confidence: 89%
“…Women initiating ART at later gestational ages have less time in HIV care and possibly less counselling than women who start ART earlier in pregnancy. This may influence retention, although the data are mixed [ 28 ]. While the underlying mechanisms require further investigation, it is also possible that late gestation at ART initiation reflects suboptimal health-seeking behaviour more generally [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…When compared to studies done in other countries of SubSaharan Africa, the adherence level in our study is slightly higher than those reported from Nnewi in Nigeria (78.3%), Lagos in Nigeria (80.6%), and Kisumu in Kenya (82%), but lower than that reported from western Kenya (89%). [21][22][23][24] This may reflect differences in the PMTCT option used, as most of these studies focused on Option A PMTCT; Option A is a different strategy for PMTCT care and support to Option B+. This difference could have had an effect on the adherence level, as the latter may be considered a simplified option.…”
Section: Discussionmentioning
confidence: 94%
“…We found that a lower level of education and being a housewife or unemployed predicted LTFU. Higher education, which may influence employment status, has been shown to improve cART adherence, as well as retention in care (Ayuo et al, 2013; Bardeguez et al, 2008; Panditrao et al, 2011). We also found that fewer ANC visits and shorter duration of cART during pregnancy predicted LTFU, which aligns with previous findings that late presentation to ANC is associated with postpartum LTFU (Panditrao et al, 2011).…”
Section: Discussionmentioning
confidence: 99%